SME Perception of Planning in Supply Chain Management to Maintain Quality Consistency - Miharja, Rediawan; Muzayanah, Fety Nurlia; Avionita, Venni (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This posts specifically examines perceptions of planning in supply chain management to maintain consistent quality of implementation in SME Bandung Raya. This study aims to determine the relationship between variables when applied to small food and beverage businesses, as well as provide recommendations for increasing business competitiveness to business actors and stakeholders related to SMEs in Bandung Raya. The lack of research on SMEs related to Supply Chain Quality Management (SCQM), Quality Performance, and Strategic Planning is the background for this study. The results of the literature review show that strategic planning is related to SCQM, but it has not been strongly proven empirically, especially in SMEs. The study method uses a quantitative approach and explanatory descriptive analysis, carried out on small food and beverage category businesses in Bandung Raya with a sample of 150 SMEs. The research results gave rise to a concept or model that is already strong. The influence of strategic planning on SCQM was recorded as significant at 0.887. The influence of SCQM on quality performance is significant at 0.829. The influence of strategic planning on quality performance through SCQM is significant at 0.736. SME perceptions are similar to those of strategic planning, and SCQM concludes that inadequate assessment, strategic communication, and the purpose and worth of SME goods can all contribute to this influence.